Getting Through COVID-19: The Pandemic’s Impact on the Psychology of Sustainability, Quality of Life, and the Global Economy – A Systematic Review - El Keshky, Mogeda El Sayed; Basyouni, Sawzan Sadaqa; Al Sabban, Abeer Mohammad (Frontiers in Psychology, 2020)
The COVOD-19 pandemic may affect the globe severely in terms of quality of life, sustainable development with its political, environmental, and economic aspects, and the global economy. Its impact is attested to by the number of research studies on it. It. The main aim of this study is to evaluate the impact of COVOD-19 on the psychology of sustainability (quality of life), on sustainable development, and on the global economy. Changes in psychological sustainability link with people’s living styles and how they deal with life situations, which is why this study focuses on the impact of COVID-19 on the psychology of sustainability. It concludes that there are multiple uncertainties because the outbreak of coronavirus disease affects not only individuals but also the world. A change in management styles is required for the operation of businesses and companies to reduce the chance of crises. The adoption of a networked hierarchical distributed leadership style, cross-training practices, and flexible guidelines would benefit. corporations in tackling the COVID-19 related crises. People are suffering from a lack of confidence and the infection scenario. There is less concern about infection prevention, as most people do not have access to infection control measures.